Greenly prepared antimicrobial cotton fabrics using bioactive agents from Cupressaceae pods - Syed, Murtaza Haider; Mior Ahmad Khushairi, Mohd Zahari; Qutaba, Syed; Norhayati, Abdullah; Syed, Lubna; Abro, Zamir Ahmed (ICE Publishing, 2022)
Antimicrobial fabrics have become essential in organizing and managing infestation and reducing odor formation by microbes. Various green sources add antimicrobial properties to fabrics, particularly cotton. However, the major problem with microbial fabrics is the reduction in antimicrobial activity after each wash. Cupressaceae pods have shown natural potential as an antimicrobial agent in herbal medicine. This study utilizes Cupressaceae for incorporating antimicrobial properties in cotton fabrics. After methanolic extraction of the Cupressaceae extract, it was applied to cotton fabrics. The application of the extract to cotton fabrics was performed by optimizing concentration, temperature and pH parameters. The extract-modified cotton showed the best performance at a 15 wt.% concentration, 140°C and pH 7.5. The treated fabrics were tested in the presence and absence of a binder using the standard washing method ISO 105-C10:2006. The mordant-treated fabric retained 16.4% more activity after 20 washes. Finally, the antimicrobial activity of the greenly developed antimicrobial cotton fabrics was checked against Staphylococcus, Escherichia coli, Bacillus and Candida albicans by using the AATCC 100-2004 test method. The study indicated that the prepared cotton fabric showed better antimicrobial activity against the earlier mentioned strains, except for C. albicans. The prepared antimicrobial fabric showed a wide range of antimicrobial activities and a lower fungal activity. Thus, the prepared fabric can be used for wound dressings, hospital staff gown material and athlete’s sportswear to prevent microbial infection.